Breaking Barriers to Climate Justice. (May 2013) - Foran, John; Widick, Richard
Sociologists John Foran and Richard Widick explore the nature of the current global impasse on climate change negotiations, and argue that an emerging alliance among progressive nations and climate justice movements, and especially youth, offers grounds for cautious optimism.